Doctors for Global Health Statement on Gaza - Doctors for Global Health (Social Medicine Publication Group, 2024)
We, Doctors for Global Health, write with a broken heart, this letter to publicly condemn the horrific atrocities ongoing in Gaza, which the  United Nations (UN) Special Rapporteur has stated that there are "reasonable grounds" to declare a genocide